A DESIGN OF A WEB-BASED VILLAGE POPULATION DATA RECORDING INFORMATION SYSTEM - Agie Nindu Ari Ginting; Agung Purnomo Sidik; Randi Rian Putra (Sean Institute, 2023)
According to the Ministry of Villages, Development of Disadvantaged Regions and Transmigration of the Republic of Indonesia (Kemendes RI), population digitalization is an effort to change traditional methods for recording and managing village population data into a more efficient and digitally integrated system. This research discusses how recording village population data is an important aspect of village administration. Accurate, up-to-date and easily accessible population data is very necessary for development planning, decision making and effective delivery of public services. However, many villages still face challenges in manually recording and managing population data, which is prone to errors, data duplication and access difficulties. In the era of digitalization and development of information technology, implementing a web-based information system can be an effective solution for increasing efficiency and accuracy in recording village population data. By using a web-based information system, village officials can record, manage and access population data automatically and in real-time. This system also allows centralized data integration, thereby reducing data duplication and making comprehensive data processing easier.